Development of Islamic Historiography in Indonesia - Anggy Giri Prawiyog; Arga Adha Anwari; Ajid hakim; Haerudin Haerudin (Universitas Majalengka, 2025)
This research carries the theme of the development of Islamic historiography in Indonesia with a focus on the methods of writing Islamic history, the influence of traditional literature, and other relevant topics. The development of Islamic historiography in Indonesia through historical research methods namely heuristics, criticism, interpretation, and historiography collected by researchers from various sources such as books, articles, and similar studies that discuss the theme of Islamic historiography in Indonesia. In the context of writing Islamic historiography in Indonesia, the writing method can be divided into two things, namely first, Islamic history is an inseparable part of the history of Muslims globally and holistically. Second, Indonesian Islamic historiography is understood as an integral part of Indonesian national history. Variations of Islamic historiography writing in Indonesia are manifested in various forms such as hikayat, khabar, silsilah and tambo. Topics of study in Indonesian Islamic historiography include local history, multidimensionality, and biographies of national figures. Historians try to reconstruct the history of Indonesian Islam by taking various sources from traditional historical records, Dutch colonial records, and modern historiography.